Association between skinfold thickness and neck circumference with anemia in rural school going adolescent girls - Kavthekar, Saiprasad; Chougule, Ashok; Kurane, Anil; Kulkarni, Devayani (International Journal Of Community Medicine And Public Health, 2017)
Background: Anemia is one of the most common hematological abnormalities found in children and adolescents. Unfortunately assessment of nutritional status of adolescent girls has been the least explored area of research, particularly in rural India. There are studies which associated Body Mass Index and anemia in adolescent girls. But the validity of BMI across diverse samples of youth has not been evaluated. Objective of this study was to study association between skinfold thickness and neck circumference with anemia in rural school going adolescents. Methods: A prospective study was carried out among 1200 rural adolescent girls of 10 randomly selected government schools (120 girls from each school and from each class 30 girls) between the age group of 12-16yrs. Skin fold thickness was measured by Herpenden’s caliper. Neck circumference was measured. The hemoglobin levels were estimated by cyanmethemoglobin method by finger prick. The collected data was statistically analysed. Results: The prevalence of anemia in rural school going adolescent girls was 54.2%. 91.3% adolescent girls had SFT <14.5mm, out of that 56.2% adolescent girls were significantly anemic. 25.1%, 30.3% and 0.7% suffered significant mild, moderate and severe anemia respectively. 84.4% adolescent girls had neck circumference <27cms, out of that 58.4% girls had significant anemia (24.2% mild, 33.4% moderate and 0.9% severe anemia). Conclusions: The adolescent girls who had SFT <14.5mm and neck circumference <27cms suggesting undernutrition were significantly anemic. SFT and NC can be used as nutritional parameter in adolescent girls. The health and nutritional education should be advocated to rural adolescent girls.